PENGALAMAN KOMUNIKASI PEMAKAIAN JILBAB FASHIONABLE: Puji Prihandini - Jurnal COMMED (Commed : Jurnal Komunikasi dan Media, 2016)
The background of this research was based on the use of a hijab no longer as a symbol of compliance withreligion but also shifted to art dressing today not less in a modern dressing generally and liven up with theestablishment komunitas-komunitas muslim who is also concerned on fashion muslim fashion, one of them isa community hijabers. Community hijabers constitute a community muslim women very concerned onfashion veil the first in indonesia.This study attempts to looked at how self concept, experience transedentalcommunication, communication interpersonal, communication groups in the veil fashionable communitymembers hijabers bandung. This research in a qualitative study by approach descriptive.And use the theorythe social act of the symbolic interaction as a theory.Data collection method used is through observation andinterviews.But the key informants based on with researchers own observations about the hijab fashionablehijabers members.The result showed that members hijabers feel the concept of her better when afterberjilbab, but in communication transedental, members are more diligent to follow recitation and islamicfirm in knowledge.In communication interpersonal, verbally is changed in the use of language but some,while based on a non verbal trying to improve his behavior when mix, especially to non-muhrim.